Anticoagulation quality through time in therapeutic range in Sub-Saharan Africa: a systematic review and meta-analysis - Demsie, Desalegn Getnet; Addisu, Zenaw Debasu; Tafere, Chernet; Feyisa, Kebede; Bahiru, Bereket; Yismaw, Malede Berihun; Mihret, Getahun; Tilahun, Abere; Gebrie, Desye; Berhe, Derbew Fikadu (Frontiers in Medicine, 2025)
BackgroundThe quality of anticoagulation with warfarin is often assessed through the time in therapeutic range (TTR). However, achieving optimal TTR and maintaining therapeutic INR levels presents significant challenges in Sub-Saharan Africa. This review aims to summarize the existing evidence on the quality of warfarin anticoagulation among patients in Sub-Saharan Africa.MethodWe searched MEDLINE via Ovid, PubMed, Embase via Ovid, and Scopus, and citation analysis from Google Scholar. The review’s primary focus was therapeutic INR and TTR ≥ 65. Meta-analysis was conducted using R version 4.3.3. A mixed-effects meta-regression model was used to examine the influence of moderators, with heterogeneity estimated using I2 and prediction intervals (PI), and publication bias assessed through funnel plots and Egger’s test, with p < 0.05 indicating potential bias. The robustness of pooled proportions was tested using a leave-one-out sensitivity analysis. The preparation of this review adhered to the guidelines outlined in the PRISMA.ResultsWe identified 15 observational studies for inclusion in this systematic review and meta-analysis. Egger’s test confirmed an absence of publication bias across these studies. Sensitivity analyses showed consistency in individual therapeutic INR (pooled estimate: 0.37; range: 0.37–0.40) and TTR (pooled estimate: 0.16; range: 0.15–0.17), closely aligning with pooled proportions. Meta-analysis of high-quality TTR measurements yielded a pooled prevalence of 17% (I2 = 89%), with study-specific values ranging from 10 to 29% and predicted effect sizes between 0.05 and 0.34. The therapeutic INR was observed at a pooled prevalence of 40% (I2 = 86%; prediction interval: 0.16, 0.67).ConclusionWarfarin therapy is associated with very low percentage of TTR suggests poor quality of anticoagulation management. Sensitivity analyses confirmed the robustness of these findings.